Analysis of the Bay of Bengal cyclone and its rejuvenation in the Arabian Sea after passing over peninsular India - Abhishek Kumar; Arun Chakraborty; Akshay Kumar Sagar (Geomatics, Natural Hazards & Risk)
Tropical Cyclone (TC) Gulab-Shaheen in the Northern Indian Ocean in September 2021 marked an extraordinary and rare climatic event that formed during the monsoon season, making it uncommon. The western North Pacific subtropical High (WNPSH) branch over the northeastern part of India is responsible for the westward movement of the Gulab cyclone in the Bay of Bengal (BoB). The extension of WNPSH and availability of soil moisture influences the cyclone’s movement over the Indian land, and it eventually emerges as a westward-moving cyclone Shaheen in the Arabian Sea (AS). Furthermore, the fourth stage of the Madden-Julian Oscillation propagated over southeast Asia is responsible for aiding cyclogenesis by increasing convective activities and maintaining higher humidity with lower wind shear. Due to this, TC Gulab remains a basic cyclonic flow over the land and moves westward after landfall. In the case of Shaheen, higher tropical cyclone heat potential and SST assisted the remnant of Gulab in rejuvenating over the AS, and lower VWS lets the storm’s center line up vertically, which helps it get more robust. Therefore, this study demonstrates the causes of the cyclone formation in BoB and its rejuvenation in the AS after surviving over the peninsular India.